2018
DOI: 10.4235/agmr.18.0032
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Elderly Onset Headache With Occurrence of Poor Functional Outcome, Cardiovascular Disease, and Cognitive Dysfunction During Long-term Follow-up

Abstract: Background: Although the frequency and intensity of headaches decrease in older adults, headaches in this population are still an important neurological disorder. The purpose of this study was to investigate the associations of headache characteristics in older adults with the development of cardiovascular disease and cognitive dysfunction. Methods: We prospectively enrolled 125 older (≥ 65 years old) patients with headache who were making their first visit to outpatient clinics and who had no prior history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…[ 30 ] In addition, several studies have reported risk factors associated with poor neurologic outcome in elderly stroke populations. [ 31 32 33 ] Findings indicate that women were more likely to have a poor outcome than men. While hormonal factors and comorbid function are known to contribute to the poor functional recovery in older women, our study reveals that well-established factors including previous stroke,[ 34 35 ] AF,[ 36 ] heart failure,[ 37 ] antidepressant use,[ 38 ] higher blood glucose level,[ 39 ] higher heart rate,[ 40 ] and rtPA administration[ 41 ] are all linked to worsening outcome in the elderly patient population.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] In addition, several studies have reported risk factors associated with poor neurologic outcome in elderly stroke populations. [ 31 32 33 ] Findings indicate that women were more likely to have a poor outcome than men. While hormonal factors and comorbid function are known to contribute to the poor functional recovery in older women, our study reveals that well-established factors including previous stroke,[ 34 35 ] AF,[ 36 ] heart failure,[ 37 ] antidepressant use,[ 38 ] higher blood glucose level,[ 39 ] higher heart rate,[ 40 ] and rtPA administration[ 41 ] are all linked to worsening outcome in the elderly patient population.…”
Section: Discussionmentioning
confidence: 99%